Herd solutions from genetic evaluations can be used as a tool to rescale the expected expression of genetic potential in cattle. (25th May 2021) - Kenny, David; Sleator, Roy D.; Murphy, Craig P.; Evans, Ross D.; Berry, Donagh P.
Abstract: The objective of this study was to determine whether response to selection for carcass weight (CW), conformation (CC) and fat (CF), and the association between heterosis and carcass performance varied by herd environment in cattle. Following edits, carcass information was available for 4, 616, 761 cattle, of which the majority were some crossbred combination of the following breeds: Angus, Aubrac, Belgian Blue, Blonde d'Aquitaine, Charolais, Hereford, Holstein‐Friesian, Jersey, Limousin, Saler, Shorthorn and Simmental. Herd environment was defined separately for each carcass trait using herd solutions outputted from carcass trait genetic evaluations. A total of 3, 859 herds were stratified, for each trait, into one of five strata based on their corresponding percentile herd solution rank, with the response to selection and the effect of heterosis then estimated within each stratum. The response in CW and CC from selection on the respective estimated breeding values (EBV) increased between the lowest (0.71 kg and 0.89 CC score increase per unit increase in the respective EBV) and highest (0.99 kg and 1.25 CC score increase per unit increase in the respective EBV) corresponding herd stratum. The response in CF from selection on CF EBV, however, reduced between the lowest and highest CF herd stratum (respective increases of 0.93 and 0.83 CF scores per unit increase in CF EBV). In addition, the effect of a unit increase in heterosis coefficient on CW, CC and CF also varied by herd stratum. Furthermore, results (i.e. the area under relative operating characteristic curves) from the present study demonstrated that the response to selection and heterosis effects estimated for the different herd stratum can be used, along with EBVs and the herd solutions themselves, to improve the accuracy of phenotypic predictions. Results from the present study could help producers to make more informed breeding decisions that are bespoke to their herd.